محاولات معهد دار السلام كونتور للبنات الثاني في تكوين البيئة اللغوية لإكساب مهارة الكلام العربي لطالبات السنة الأولى بكلية المعلّمات الإسلاميّة - Abdul Hafidz Zaid (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
Modern Islamic Boarding School of Darussalam Gontor (MIBS Darussalam Gontor) is one of the famous Islamic educational institutions with the curriculum of Arabic and English language. Indeed the purpose of learning Arabic language in this boarding school is to prepare students to master the Arabic language, because Arabic language will become the key to all sources of Islamic knowledge. Among the main methods to pursue and learn Arabic is to create a good language environment. The purpose of this research is to know the methods of MIBS Darussalam Gontor especially MIBS Darussalam Gontor for Girls 2 in forming a good language environment in order to maximize the students' language skills. The method of this research is descriptive qualitative. This method is used to know the description of the existing situation in the field, which in this case is MIBS Darussalam Gontor for Girls 2. The results of this study indicate that MIBS Darussalam Gontor for Girls 2 has established or provided a good language environment. The institute prepares students in the first year as a foundation in Arabic language learning. But most of the first graders are not used to speaking in Arabic, so they need a great help, which in this case can be helped by various activities that use Arabic as the language of instruction. MIBS Darussalam Gontor for Girls 2 does a lot of effort to establish a language environment that can be classified to two parts, academic in the classroom and non-academic in the dormitory or outside the classroom.